Efficacy of Piccha Basti and immune enhancer medicines in the management of ulcerative colitis - Pooja Sharma; Divya Kajaria (Wolters Kluwer Medknow Publications, 2022)
Ulcerative colitis (UC) is an immune-mediated disease; the intestine contains an enormous colitis antigenic load derived from the food and microbial flora. There appear to be four main factors which influence the disease: host genetic susceptibility, a dysregulated immune response, impairment of intestinal epithelial barrier function, and environmental factors. According to Ayurveda, it may be correlated with Raktatisara, which is mentioned as advanced stages of Pittatisara with similar signs and symptoms. A 19-year-old female patient was diagnosed with UC in May 2018, with the complaints of frequent defecation of stool mixed with blood and pain in the abdomen. She consulted allopathic physician and where the patient was diagnosed with UC through sigmoidoscopy, colonoscopy, and biopsy. The patient was on conservative treatment for 2 months. The patient gradually developed the following symptoms like bilateral pain in all major and minor joints, hair loss, reddish discoloration on both medial aspect of thigh and hips. After getting no relief, the patient visited outpatient department of AllA, Sarita Vihar, New Delhi. The patient was admitted to the inpatient department of AIIA hospital. After the 41 days of treatment, stool examination shows no occult blood in stool, followed by 2 months follow-up and the patient got 80% relief in all the signs and symptoms. Piccha Basti along with oral medicines is highly effective in the management of Raktatisara. This case report highlights the efficacy of Piccha basti and immune enhancer medicines in the management of UC and provide a better pathway for this disease.